A NEW RECORD OF THE PHYLLOCARID CRUSTACEAN (CRUSTACEA: PHYLLOCARIDA) IN THE SERPUKHOVIAN (MISSISSIPPIAN) OF THE DONETS BASIN, UKRAINE - DERNOV, Vitaly (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The Carboniferous phyllocarid crustaceans of the Donets Basin are not well studied and are represented by the genus Dithyrocaris and undefined remains referred to Phyllocarida indet. The study of fossil phyllocarids is of great palaeobiogeographical importance, at least for the Carboniferous marine palaeobasins of the northern hemisphere. Methods. Two specimens of carapace valves of the phyllocarid Ceratiocaris sp. are examined in this study. The fossils originate from the Serpukhovian of the western Donets Basin, eastern Ukraine. The Serpukhovian deposits in the Donets Basin are represented by the Samara Formation and most of the Kalmis Formation, but it is impossible to determine which formation the studied material comes from. Results. The described Ceratiocaris sp. is very similar to Ceratiocaris truncatus Woodward, 1871 in terms of the outline of the valve. However, there are some differences, namely: the described valve is somewhat wider compared to the Ceratiocaris truncatus, the line of the greatest width of the studied valve is between its centre and the anterior part, while in Ceratiocaris truncatus the ventral and anterior margins form a semi-elliptical line. The posterior margin of Ceratiocaris sp. is wider and more concave than that of Ceratiocaris truncatus, while the rostral notch is narrower and shallower. Ceratiocaris sp. differs from Ceratiocaris oretonensis Woodward, 1871, in the outline of the valve: in C. oretonensis it gradually narrows anteriorly, while in C. sp. it widens rapidly to about 33 % of the valve length and then sharply narrows. In addition, the posterior margin of Ceratiocaris oretonensis is much more concave and narrower. Conclusions. In the Carboniferous succession of the Donets Basin, phyllocarids are predominantly distributed in the Bashkirian interval. Only two taxa, Dithyrocaris granulata doneziana Riabin, 1921 and D. tricornis aisenvergi Krestovnikov, 1961, occur from outside the Bashkirian interval, namely the Serpukhovian and Upper Pennsylvanian, respectively. Thus, today, Carboniferous phyllocarids in the Donets Basin are represented by only two genera, Dithyrocaris Scouler in Portlock, 1843 and Ceratiocaris M’Coy, 1849.